(untitled) (Innovative professional education, 2025)
Modern digital tools significantly enhance the assessment of knowledge in vocational education. This article examines the key digital platforms used for testing knowledge in lathe work, including adaptive systems and artificial intelligence technologies. The advantages, disadvantages, and effectiveness of these tools in the educational process are analyzed. A practical case of implementing digital testing technologies in the training of future lathe operators is presented, along with a comparison of digital testing with traditional assessment methods